Annotated bacterial chromosomes from frame-shift-corrected long-read metagenomic data - Arumugam, Krithika (Microbiome, 2019)
BACKGROUND: Short-read sequencing technologies have long been the work-horse of microbiome analysis. Continuing technological advances are making the application of long-read sequencing to metagenomic samples increasingly feasible. RESULTS: We demonstrate that whole bacterial chromosomes can be obtained from an enriched community, by application of MinION sequencing to a sample from an EBPR bioreactor, producing 6 Gb of sequence that assembles into multiple closed bacterial chromosomes. We provide a simple pipeline for processing such data, which includes a new approach to correcting erroneous frame-shifts. CONCLUSIONS: Advances in long-read sequencing technology and corresponding algorithms will allow the routine extraction of whole chromosomes from environmental samples, providing a more detailed picture of individual members of a microbiome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40168-019-0665-y) contains supplementary material, which is available to authorized users.